1980
DOI: 10.1063/1.327383
|View full text |Cite
|
Sign up to set email alerts
|

Complex free-carrier profile synthesis by ’’atomic-plane’’ doping of MBE GaAs

Abstract: Doping solely during periods when growth was suspended has been used to synthesize profiles not easily achieved by conventional doping techniques. Suspension of growth under arsenic stabilized conditions allows Ge doping to produce n-type complex profiles with reduced autocompensation. At higher temperatures, autocompensation becomes apparent. Under gallium stabilized conditions, heavily autocompensated n-type layers resulted, consistent with a nonunity incorporation coefficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(25 citation statements)
references
References 11 publications
0
25
0
Order By: Relevance
“…Delta-doping (d-doping) technique [2][3][4][5][6] have been early used for improving the performance of GaAs III-V compound semiconductors. There are several advantages for the use of Si d-doping GaAs when compared to uniform doping, such as enhanced electron concentration, reduced compensating defects and improving the temperature-related stability.…”
Section: Introductionmentioning
confidence: 99%
“…Delta-doping (d-doping) technique [2][3][4][5][6] have been early used for improving the performance of GaAs III-V compound semiconductors. There are several advantages for the use of Si d-doping GaAs when compared to uniform doping, such as enhanced electron concentration, reduced compensating defects and improving the temperature-related stability.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In ␦-doped structures a two-dimensional electron gas ͑2DEG͒ can be formed with a much higher freeelectron density as compared to the modulation doped heterostructures, 3,4 and a higher electron mobility as compared to bulk-doped semiconductors. 5 These are important effects for applications in high-speed electronics 6 and in optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…This result is supported by the observation of very sharp CV profiles for high density Si planes in GaAs grown by flow-rate modulation epitaxy, a variant of MBE which also uses gaseous sources [32], and by crosssectional transition electron microscopy (TEM) imaging of Be 8-planes, which appear broader in MBEgrown layers than in GSMBE-grown layers [33]. In contrast, Asom et al [34] have found no difference in the FWHM of CV or SIMS profiles of Si or Be 8-planes in GaAs, when the As was supplied as As4, As 2 or from ASH3; they attribute their results to the low sheet density of impurities which they used in their experiments, but although concentration-dependent segregation effects are indeed observed, it is still not clear how this relates to the As species used.…”
Section: Surface Segregationmentioning
confidence: 97%
“…Wood et al [2] then described its application to the generation of tailored dopant profiles in Ge-doped GaAs grown by MBE: by depositing a series of closely-spaced 8-doped planes, with different areal densities of impurity on each plane, it was possible to simulate complex doping profiles without the need to change the flux of atoms from the Ge cells. Another early application was the planar-doped-barrier diode, as demonstrated by Malik et al [3], who employed a fully-depleted p-type 8-doped plane to produce a triangular electrostatic barrier, which was used to control the electron current in the device.…”
Section: Introductionmentioning
confidence: 99%